Long-term PM2.5 exposure and new-onset lung diseases among middle-aged and older adults in China: a retrospective cohort study from CHARLS - Xiaojun Wu; Kai Zhang; Daihua Yu; Jingjing Li (Frontiers in Public Health)
BackgroundAir pollution caused by ambient fine particulate matter (≤ 2.5 μm) adversely affects human health. Previous studies have shown that PM2.5 exposure increases the risk of lung diseases. However, the relationship between long-term PM2.5 exposure and new-onset lung diseases among middle-aged and older adults in China is still unclear.MethodsWe conducted a retrospective cohort study through the China Health and Retirement Longitudinal Study (CHARLS) and Science Data Bank (ScienceDB). The logistic regression model and restricted cubic spline (RCS) were used to explore the relationship between long-term PM2.5 exposure and new-onset lung diseases. To further increase the robustness of the results, we performed sensitivity and subgroup analyses.ResultsA total of 10,707 patients were included in this study. The 10,707 patients were divided into two groups: without new-onset lung diseases (n = 9,019) and with new-onset lung diseases (n = 1,688). The results of multivariate analysis showed that per 1 ug/m3 increase in annual PM2.5 concentration, the risk of new lung diseases increased by 0.3%. The results of the RCS showed that PM2.5 exposure increased the risk of new-onset lung diseases more significantly when the annual PM2.5 concentration was greater than 48.5 ug/m3. Sensitivity analysis and subgroup analysis also confirmed the reliability of the results.ConclusionPM2.5 exposure increases the risk of new-onset lung diseases among middle-aged and old adults in China, especially when the concentration of PM2.5 > 48.5 ug/m3. Our study established an empirical foundation for refining PM2.5 emission regulations, developing age-stratified screening protocols for incident pulmonary diseases, and advancing mechanistic investigations into PM2.5-induced lung pathology.